2017
DOI: 10.4236/ojfd.2017.74041
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Natural Convection of Air in a Square Cavity with Partially Thermally Active Side Walls

Abstract: In this present work, we study heat transfer in a confined environment. We have to determine the thermal and dynamics fields of the cavity while observing the effect of the Rayleigh number which depends on the characteristics of the fluid and the temperatures imposed. The behavior of boundary layers in natural convection is analyzed along this square cavity. The central halves of its vertical walls are heated at different temperatures. The left active part is at a higher temperature than the one on the right w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…The outcomes are presented for Rayleigh number = Ra t o 10 10 , 3 5 Prandtl number = Pr 6.5, Darcy number = -Da 10 4 to -10 2 and length of each heated rod = Lt 0.2 to 0.5. Numerical investigation is executed to find the impact of these parameters on flow fields and thermal distributions as presented in figures (3)- (11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes are presented for Rayleigh number = Ra t o 10 10 , 3 5 Prandtl number = Pr 6.5, Darcy number = -Da 10 4 to -10 2 and length of each heated rod = Lt 0.2 to 0.5. Numerical investigation is executed to find the impact of these parameters on flow fields and thermal distributions as presented in figures (3)- (11).…”
Section: Resultsmentioning
confidence: 99%
“…Rostami et al [10] numerically and experimentally reviewed the free convection in different shaped enclosures. Kane et al [11] considered natural convective flow in a partially heated enclosure. Basak et al [12] observed the influence of uniform and non-uniform thermal conditions in an isosceles triangular cavity.…”
Section: Introductionmentioning
confidence: 99%
“…A similar analysis has been conducted by Valencia and Frederick 17 with partially active walls. The role of partially heated verticals on heat transfer in air of square enclosure has been reported by Kane et al 18 Recent studies of natural or mixed convection in a square cavity filled with different fluids and with different supplementary effects (eg, magnetic body forces, lid‐driven boundary, etc) have been presented in References 19–25 …”
Section: Introductionmentioning
confidence: 92%
“…Reference [2] studied natural convection of air in a square cavity with partially thermally active side walls. The behavior of boundary layers at variable Rayleigh numbers was analyzed.…”
Section: A Review Of Previous Related Studiesmentioning
confidence: 99%